Valley of the Dolls : A Novel - Susann, Jacqueline; Introduction by Burchill, Julie (London Virago, 2003)
This Cinderella story revolves around 3 pill-popping showbiz women: Anne, Jennifer, and Neely, a ruthless understudy turned superstar. Together they learn the hard way that fame, fortune, beauty and stardom don't always equal happiness.
Keywords: California--Los Angeles--Hollywood -- Female friendship -- Women--Drug use -- Motion picture industry